O capital social e suas funções na sociedade empresária - Hübert, Ivens Henrique (2007)
The aim of this dissertation is to perform a broad study about the capital stock under Brazilian law. Its intention is to analyze the most relevant legal norms that structure the capital stock amongst Brazilian societies, especially companies. This study on capital stock makes a clear option for an analysis that emphasizes, above all, the functions that it fulfills, structured by legal principles which are central to this discipline. From the study of these presuppositions, sustained by a deep analysis of how principles and functions conduct the interpretation of legal rules, the main problems regarding the notion of capital stock are verified, situated, and discussed. Thus, this dissertation begins with the establishment of the fundamental presuppositions for the analysis, so to, after that, verify which principles and functions are essential in order to structure the whole discipline of the capital stock. Once all these introductory aspects are duly situated, the study examines diverse issues related to the discipline of the capital stock and its treatment by national law. Especially, this study delimitates and defines, with greater precision, the central problem of the whole structure of the capital stock: the thin capitalization. This study tries to verify its causes, which derive from corporate and fiscal reasons, its effects, as well as the possibilities regarding the treatment of this phenomenon. Besides this central issue, this study intends to examine some specific situations that refer to the theme, as the increase and decrease of capital stock and the problems that arise from the subscription and payment of capital stock. After all these points are examined, it is the goal of this analysis to achieve some conclusions regarding the deficiency in the regulation of this topic and the possibilities that it offers, taking its functions into account